2007
DOI: 10.1179/136485907x176481
|View full text |Cite
|
Sign up to set email alerts
|

Entomological evaluation of three brands of manufactured insecticidal nets and of nets conventionally treated with deltamethrin, after repeated washing

Abstract: The present study evaluated the efficacy and wash resistance of three types of commercial, deltamethrin-treated nets (PermaNet, Yorkool and A-Z nets) - that their manufacturers claimed to be long-lasting insecticidal nets (LLIN) - and those of nets conventionally treated with deltamethrin, at either 23-27 mg/m(2) (using one K-O Tab tablet/net) or 46-54 mg/m(2) (using two K-O Tab tablets/net). The nets were tested unwashed or after being washed, by hand or machine, five or 15 times. After each wash, the nets we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 5 publications
2
18
1
Order By: Relevance
“…In previous studies, the wash resistance of PermaNet2 was found to be similar to the results of wash resistance of PN2 (new generation of PermaNet2) up to 15 washes. 2,17,18,20,21 In the present study, the results showed better wash resistance of PN2 in comparison to PermaNet2 up to 21 washes. 21 22,23,26 In two studies that were carried out by Yates et al and Oxborough et al on wash resistance of KO 123, although their studies were laboratory based and they used WHO laboratory washing methods, they reported similar results to our study and confirmed that KO 123 is LLITNs.…”
Section: 15supporting
confidence: 59%
See 2 more Smart Citations
“…In previous studies, the wash resistance of PermaNet2 was found to be similar to the results of wash resistance of PN2 (new generation of PermaNet2) up to 15 washes. 2,17,18,20,21 In the present study, the results showed better wash resistance of PN2 in comparison to PermaNet2 up to 21 washes. 21 22,23,26 In two studies that were carried out by Yates et al and Oxborough et al on wash resistance of KO 123, although their studies were laboratory based and they used WHO laboratory washing methods, they reported similar results to our study and confirmed that KO 123 is LLITNs.…”
Section: 15supporting
confidence: 59%
“…Previous studies published by the first author of this study reported almost identical results (40% and 64.8% mortality in comparison to 62% mortality in the present study). 3,17 Other researchers have reported different results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[3], Hodjati and Curtis [10] and Chandre et al [11]. It is obvious that repeated washing of LLINs can result in a reduction in efficacy due to loss of insecticide [12,13]. The excito-repellent effect of the deltamethrin (LifeNet®, Permanet®) and of permethrin (Olyset®), which explains the increase of the exophily, appeared differently in the three LLINs., by considering data from the experimental huts and the tunnel tests, it can be concluded that repeated washings does not completely affect the repellent effect.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three LLINs evaluated, Olyset® and Permanet® 2.0 have been on the market the longest and are the most studied. Most of the studies carried out comparing the bio-efficacy of the two market-dominant LLINs [12] have consistently shown that Olyset® is more wash durable and less bio-effective compared to Permanet®. This may be because of the treatment technology used and netting material (Duchon S: Regeneration, wash resistance and efficacy of long-lasting insecticidal mosquito nets (LifeNet) from Bayer CropScience against susceptible mosquitoes of Anopheles gambiae , umpublished report).…”
Section: Discussionmentioning
confidence: 99%